2015
DOI: 10.4103/2278-330x.155643
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices about oral cancers among dental students in H.P Government Dental College, Shimla-Himachal Pradesh

Abstract: Aim:The aim was to assess the knowledge, attitude and practices among undergraduate dental students about oral cancer.Materials and Methods:A cross-sectional questionnaire study was conducted among undergraduate dental students between the 3rd and 5th years in H.P Government Dental College, Shimla. The questionnaire consisted of 15 questions, five each on knowledge, attitudes and practices. The data were analyzed by Statistical Package for the Social Sciences (SPSS Inc., version 16 for Windows, Chicago, IL, US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
20
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 13 publications
11
20
3
4
Order By: Relevance
“…The study identified an inequality in gender distribution, with a majority of students in both the medical and dental fields being female, similarly to previous studies conducted in Malaysian public universities. This trend, noted internationally, has not changed much from previous studies. Also similarly to previous studies conducted in Malaysian public universities, the group of medical students was larger than that of dental students, possibly because Malaysian universities usually have a much larger intake of medical students than dental students.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The study identified an inequality in gender distribution, with a majority of students in both the medical and dental fields being female, similarly to previous studies conducted in Malaysian public universities. This trend, noted internationally, has not changed much from previous studies. Also similarly to previous studies conducted in Malaysian public universities, the group of medical students was larger than that of dental students, possibly because Malaysian universities usually have a much larger intake of medical students than dental students.…”
Section: Discussionsupporting
confidence: 83%
“…found that 12.3% of medical students and 53.3% of dental students felt that they had adequate knowledge about prevention and detection of oral cancer. In India, only 25.8% of medical students and 7.5% of dental students felt that they had sufficient knowledge of oral cancer. In a positive light, most of the respondents had the desire for more knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Malaysia 96.7%, in Carter and Ogden 72.46%, and in Shimla/India 89.7% of dental students affirmatively replied that they do routine oral mucosa examination. Additionally, our results are comparable to results by Brzak, Awan & Fotedar et al [6][7][8] who reported that the majority of dental students under study routinely examine oral mucosa) [7][8][9]. In the present study, the majority of students were able to identify tobacco (95.7%) as the principal risk factor for oral cancer.…”
Section: Discussionsupporting
confidence: 81%
“…Unfortunately, almost more than half of the students (51.5%) did not recognize human papillomavirus (HPV) or alcohol consumption as evolving oral cancer risk factors. The same trend was reported in Malaysia, where 84.4% of dental identified tobacco consumption as a risk factor for oral cancer, but lesser percentage was going for alcohol consumption 35% [8]. In accordance with our results, a previous study was done to assess oral cancer awareness of Romanian undergraduate dental students; they found that 96.8% recognized tobacco as the first oral cancer risk factor, unlike our results a higher percentage was found for previous oral cancer lesion (85.1%), and alcohol consumption (77.7%) [10].…”
Section: Discussionsupporting
confidence: 59%